Study on Curve Passing Capacity of Independent Wheelset on Light Rail Vehicles - Yongxiang WEN; Wenxiang ZHOU; Yang CHEN; Zhen ZHANG; Xiaoyang ZHANG (机车电传动)
Aiming at the application of independent wheelset in light rail vehicles, a new structure of independent wheelset, which combined planetary differential and lower axle, was studied. The structure could improve the steering ability of independent wheelset.Through the analysis of several mainstream LRV structures, it was shown that reasonable vehicle structure types could improve the curve passing performance of vehicles, among which the float type bogie steering was the most flexible and the bogie could cross the curve radially, which was conducive to reducing wheel-rail abrasion and noise. At the same time, the bogie types of low floor light rail vehicles at home and abroad were studied. It was found that the use of independent wheelset bogies could easily meet the 100% low floor rate of light rail vehicles. The simulation results showed that the independent wheelset with active control could pass through the small radius curve radially.